Low CBS expression can identify patients who benefit from adjuvant chemotherapy in gastric cancer. Issue 11 (2nd November 2021) - Zhao, Jinsheng; Zhao, Yusheng; Ding, Shasha; Liu, Tao; Meng, Fanzheng
ABSTRACT: Aim: To explore the clinical significance of Cystathionine beta-synthase (CBS) expression in gastric cancer (GC). Research design and methods: CBS expression and clinicopathological/follow-up information of patients with gastric cancer undergoing operation were collected from The Cancer Genome Atlas (TCGA) database. The association of CBS expression with patients' overall survival (OS) was determined in the entire cohort and different subgroups. Validation was performed in two external cohorts from NCBI Gene Expression Omnibus (GEO) database. The estimated drug response of the tumors with different CBS expressions was characterized. The potential CBS-related cellular pathways in chemoresistance were explored. Results: High CBS was associated with poor OS in patients receiving adjuvant chemotherapy (ACT) but not those without ACT. And ACT was associated with favorable OS in patients with low CBS expression but not those with high CBS expression. The results were verified in two external cohorts. Drug response prediction suggested that patients with low CBS expression showed high sensitivity to 5-Fluorouracil. Gene Set Enrichment Analysis (GSEA) suggested that CBS might contribute to GC chemoresistance via modulating many cellular pathways, including down-regulating apoptosis and P53 pathways while up-regulating DNA repair pathway. Conclusion: Low CBS expression can predict the benefit from ACT in GC.